The historical consumer : consumption and everyday life in Japan, 1850-2000 - Francks, Penelope; Hunter, Janet (Palgrave Macmillan, 2012)
A collection of studies tracing the history of consumption and daily life in Japan from the late Edo period to the modern era, exploring cultural and economic transformations